Removal of cationic dye methylene blue (MB) from aqueous solution by ground raw and base modified pine cone powder - Yagub, Musstafa; Sen, Tushar; Ang, Ha-Ming (Springer, 2013)
The adsorption capacity of raw and sodium hydroxide-treated pine cone powder in the removal of methylene blue (MB) from aqueous solution was investigated in a batch system. It was found that the base modified pine cone exhibits large adsorption capacity compared with raw pine cone. The extent of adsorption capacity was increased with the increase in NaOH concentration. Overall, the extent of MB dye adsorption increased with increase in initial dye concentration, contact time, and solution pH but decreased with increase in salt concentration and temperature for both the systems. Surface characteristics of pine cone and base modified pine cone were investigated using Fourier transform infrared spectrophotometer and scanning electron microscope. Equilibrium data were best described by both Langmuir isotherm and Freundlich adsorption isotherm. The maximum monolayer adsorption capacity was found to be 129.87 mg g-1 at solution pH of 9.02 for an initial dye concentration of 10 ppm by raw pine cone. The base modified pine cone showed the higher monolayer adsorption capacity of 142.25 mg g-1 compared with raw pine cone biomass. The value of separation factor, RL, from Langmuir equation and Freundlich constant, n, both give an indication of favourable adsorption. The various kinetic models, such as pseudo-first-order model, pseudo-second-order model, intraparticle diffusion model, double-exponential model, and liquid film diffusion model, were used to describe the kinetic and mechanism of adsorption process. Overall, kinetic studies showed that the dye adsorption process followed pseudo-second-order kinetics based on other models.